Increasing the Salt Stress Tolerance of Some Tomato Cultivars under the Influence of Growth Regulators - Mihaela Covașă; Cristina Slabu; Alina Elena Marta; Carmenica Doina Jităreanu (Plants, 2023)
Areas with saline soils are in continuous expansion, and in this context, it is very important to find solutions that help plants adapt more easily to these stress conditions, and to identify the main physiological and biochemical mechanisms involved in determining a good adaptability of plants. Biostimulants could be a plausible solution. This study was conducted in 2021 at the IULS (Iasi University of Life Sciences) in Romania, under greenhouse conditions and the biological material consisted of four tomato varieties: Buzau, Elisabeta, Bacovia, and Lillagro. For the treatments, we used natrium chloride (NaCl) 120 mM and an Atonik biostimulant. Three treatments were applied at intervals of 14 days. The Atonik biostimulant was applied by foliar spray, and the saline solution was applied to the root system. We have gathered some observations on the growth and fruiting character of the tomato plants studied: the height of the stems, the number of flowers in the inflorescence, the number of fruits, and the weight of fruits. Chlorophyll and carotenoid pigments as well as proline amino acid from leaves were also measured. Observations were made 14 days after the application of each treatment. Quantitative determinations were made 14 days after the application of the third treatment. The findings of this study made it clear that the Atonik biostimulant presented a positive effect on the physiological processes observed in tomato plants grown under salt stress conditions.